2023
DOI: 10.3390/buildings13010205
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric and Content Review of Carbon Emission Analysis for Building Construction

Abstract: To combat climate change and meet energy conservation and emission reduction goals, the building sector must adopt low-carbon technologies and low-carbon management methods. To systematically explore existing research areas and track future research trends of carbon emission in the construction stage (CECS), this study conducts a bibliometric and content analysis of CECS studies. 563 relevant publications published between 2000 and 2022 are examined and analyzed using data from the Web of Science (WoS) core co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 131 publications
0
7
0
Order By: Relevance
“…Usually, a set of best optimum solutions can be attained in a multi-objective optimization problem. A model of Pareto front 27 , 28 was chosen by taking the two differing objectives within the reasonable space defined in Eq. ( 12 ) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, a set of best optimum solutions can be attained in a multi-objective optimization problem. A model of Pareto front 27 , 28 was chosen by taking the two differing objectives within the reasonable space defined in Eq. ( 12 ) …”
Section: Methodsmentioning
confidence: 99%
“…This wide amount is mostly caused by the fact that embodied energy differs between countries. Additionally, as efforts to make net-zero energy buildings progress, these percentages will rise 27 , 28 . This is because the net-zero energy goal pertains largely to the operating energy, rather than to the life-cycle energy.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the scientific and rational selection of carbon emission factors for residential buildings, this study employed the IPCC factorial inventory method (IPCC-FIM) to calculate the carbon emissions produced from 2010 to 2019. Subsequently, the study compiled and summarized the relevant influencing factors from the existing literature [7,14,[29][30][31][32][33][34][35][36][37][38][39][40][41]. Through a detailed analysis of the sources, compatibility of research content and method-ologies, as well as the frequency of each factor, this study identified the characteristics of carbon emissions from residential buildings.…”
Section: Determination Of Carbon Emission Factorsmentioning
confidence: 99%
“…Currently, there are numerous methods for evaluating carbon emissions. Pinghai and others have reviewed the carbon emission calculations during the industrialized construction phase [1]. Zhang Zhen and colleagues conducted research on the integrated calculation and carbon reduction technology of carbon emissions during transportation hub project construction [2].…”
Section: Introductionmentioning
confidence: 99%